Photoproduction of π + π-pairs in a model with tensor-pomeron and vector-odderon exchange - Bolz, Arthur; Ewerz, Carlo; Nachtmann, Otto; Sauter, Michel David; Schöning, André (Arxiv, 2015)
We consider the reaction (gamma p) to (pi+ pi- p) at high energies. Our description includes dipion production via the resonances rho, omega, rho-prime and f2, and via non-resonant mechanisms. The calculation is based on a model of high energy scattering with the exchanges of photon, pomeron, odderon and reggeons. The pomeron and the C=+1 reggeons are described as effective tensor exchanges, the odderon and the C=-1 reggeons as effective vector exchanges. We obtain a gauge-invariant version of the Drell-Soeding mechanism which produces the skewing of the rho-meson shape. Starting from the explicit formulae for the matrix element for dipion production we construct an event generator which comprises all contributions mentioned above and includes all interference terms. We give examples of total and differential cross sections and discuss asymmetries which are due to interference of C=+1 and C=-1 exchange contributions. These asymmetries can be used to search for odderon effects. Our model is intended to provide all necessary theoretical tools for a detailed experimental analysis of elastic dipion production for which data exist from fixed target experiments, from HERA, and are now being collected by LHC experiments.
Im Titel wird pi als griechischer Buchstabe dargestellt
Im Titel sind die Zeichen + und - hochgestellt
Gesehen am 19.02.2018